Impact of Intra-Oral Dental Materials on Magnetic Resonance Imaging: A Perspective Survey from Dental Professionals - Sejal Gupta; Mathangi Kumar; Kalyana C Pentapati; Ravindranath Vineetha; Vinu Thomas George; Nidambur Vasudev Ballal; Priya Pattath Sankaran (Journal of Pharmacy and Bioallied Sciences)
Aim and Background: This study aimed to assess the awareness of dental practitioners about the impact of various intra-oral dental materials on magnetic resonance imaging (MRI). Methods: This cross-sectional questionnaire survey was conducted on dental graduates, postgraduates, and faculty who were provided with a validated self-administered questionnaire to assess their knowledge about various materials on MRI. Information regarding the interactions of these materials was classified under three categories: heat generation, mechanical vibration, and artifact production. A consensus panel of six experts from various specialties of dentistry and radiodiagnosis framed a specially designed closed-ended questionnaire over two phases. Knowledge scores were calculated based on the respondent scores. The comparison of mean knowledge scores was done using the Mann-Whitney U test. Results: Overall, 200 dental professionals participated in the study; 85.5% of the participants were aware that dental materials could interfere with MRI. Most of the participants felt that stainless-steel materials were least compatible whereas composites were most compatible with MRI. Conclusion: This study showed limited knowledge regarding the interference of dental materials in MRI. A material safety information card should be provided by the manufacturer that can be used to document the patient dental records. Clinical Significance: Continuing dental education programs should focus on educating dental professionals and reducing knowledge gaps. A material safety information card should be provided by the manufacturer for the materials that are used.